Neuroendocrine neoplasms of the head and neck - Konukiewitz, B.; Agaimy, Abbas; Weichert, W.; Kloeppel, G. (Pathologe, 2018)
Common to all neuroendocrine neoplasms (NENs), irrespective of their site of origin, is the expression of synaptophysin and chromogranin A. NENs of the head and neck region derive either from epithelial or neural/neuroectodermal tissues. The epithelial-type NENs express cytokeratins and include the well-differentiated typical and atypical carcinoids (also called low- and intermediate-grade neuroendocrine carcinomas by WHO), the poorly differentiated high-grade neuroendocrine carcinomas of small and large cell type and the mixed neuroendocrine-nonneuroendocrine neoplasms. The neural-neuroectodermal-type NENs comprise olfactory neuroblastoma and paraganglioma, each of them with distinct clinicopathological characteristics. Olfactory neuroblastomas show a spectrum of histologic differentiation and are prognostically classified by Hyams grading. Paragangliomas often occur multiple and show a familial background. Most head and neck NENs occur in the upper respiratory system. Their diagnosis follows the general guidelines for NENs, focusing on immunohistochemical profiling. Molecular examinations are so far only required in individual cases.
EVALuna2:34881